Boundary value problems of differential inclusions with Riemann-Liouville fractional derivative - Benchohra, M.; Djebali, S.; Hamani, S. (Нелінійні коливання, 2011)
In this paper, we establish sufficient conditions for the existence of solutions for a class of boundary value
problem for fractional differential inclusions involving the Riemann-Liouville fractional derivative. The
cases of both convex and nonconvex valued right-hand side are considered. The topological structure of
the set of solutions is also examined. Отримано достатнi умови iснування розв’язкiв для класу граничних задач для диференцiальних включень з похiдною дробового порядку, включаючи дробову похiдну Рiмана – Лiувiлля. Розглянуто випадки опуклої та неопуклої правої частини. Також вивчено топологiчну структуру
множини розв’язкiв.